Developing coaches` professional judgement and decision making: Using the `Big 5` - Collins, D.; Collins, L. (Journal of Sports Sciences, 2020)
Coaching can be seen, in large part, as a decision-making game in which coaches must decide on and then deploy an optimum blend of tools to best meet the needs of performance and context. Examining this concept through a lens of professional judgement and decision making, research has shown positive benefits for this approach to understanding and enhancing the coaching process and its outcomes. To date, however, there has been less attention paid to the development of simple applied tools which can be used to facilitate these skills. Accordingly, this paper describes the Big 5, a structured approach to critical reflection which can be used to improve coaching. Following its description, we present some preliminary data on the impact of the Big 5 in a sample of professional adventure sports coaches.